Hypertension knowledge, attitudes and perceptions among adults in the Navrongo Health and Demographic Surveillance Site: a mixed methods analysis - Ahaana Singh; Godfred Agongo; Samuel T. Chatio; Bernard Logonia; Cornelius Y. Debpuur; Patrick O. Ansah; Abraham R. Oduro; Kerstin Klipstein-Grobusch; Engelbert A. Nonterah (BMC Primary Care, 2024)
Abstract Background This study assessed knowledge, behaviors, and perceptions towards hypertension following community dissemination on cardiovascular disease (CVD) risk within the Navrongo Health and Demographic Surveillance Site in Northern Ghana. Methods A cross-sectional mixed methods study was conducted among middle aged men and women following education on CVD and their risk factors. Knowledge and attitudes of participants regarding hypertension were measured in 310 participants using a survey tool and the resultant data was analyzed with descriptive statistics. Focus group discussions (FDG) were used to assess perceptions of 40 study participants on their lived experiences with hypertension. Recorded interviews were transcribed verbatim and coded into themes using Nvivo 12 software before thematic analysis. Results Of the 310 surveyed participants, 54% were women and the mean age was 50 ± 6 years. The results showed that 84% of participants had heard about hypertension, 70% knew it was an increase in blood pressure and could be caused by excess salt intake, poor diet and physical inactivity. About 22.3% of participants were aware of the had hypertension. In terms of management, majority of the participants were aware that hypertension could be treated with antihypertensive medication and that untreated or uncontrolled hypertension could result in adverse health consequences. Few participants had ever had their blood pressure measured and did not access screening or healthcare care services and rather perceived the health system as inadequate to screen, and manage hypertension. Conclusion Though, knowledge on hypertension was high, awareness of hypertension status and access to screening and healthcare services was low. Community beliefs and perceptions strongly influence treatment, and control of hypertension. Effective sustained community dissemination efforts addressing misperceptions could improve hypertension treatment and control.